BEEF QUALITY IN PESANGGARAN ABBATOIR RATED FROM pH VALUE AND WATER HOLDING CAPACITY - Setiawan, Satria Yanuwardani; Swacita, Ida Bagus Ngurah; Suada, I Ketut (Buletin Veteriner Udayana, 2017)
Pesanggaran abattoir is the largest slaughterhouses in Bali. The purpose of this study was to determine the beef quality in Pesanggaran abattoirs tested from pH value and water holding capacity and the relationship between the two variables. Fifteen samples of beef taken from longisimus dorsi tested the qualities based on the pH value and water holding capacity during the process of the observation period starting at the first hour until eight. The results showed that, the quality of beef produced in Pesanggaran abattoirs has an ultimate pH 5.51 at the 7th hour after slaughter and water holding capacity with a value of 60.4% at the 7th hour after slaughter. It can be concluded that the pH and WHC of beef at Pesanggaran abattoir decreased from first hour to 7th hour and there are positive correlation between pH and WHC of beef.
Keywords: Daging sapi; kualitas daging; nilai pH; daya ikat air